Dye removal from aqueos solution by using treated sugarcane bagasse at various pH - Saiful Azhar, Saad; Abdul Ghaniey Liew, Abdullah; Suhardy, Daud; Farizul Hafiz, Kasim (School of Materials Engineering, 2009)
The use of low cost, recycled waste and ecofriendly adsorbents has been investigated as an alternative method for replacement of currently expensive method for removing dyes from wastewater. In this study, sugarcane bagasse - an agro industry waste were used to remove the dyes from the aqueous solution in a batch reactor. The formaldehyde treated (PCSB) and sulphuric acid treated (PCSBC) sugarcane bagasse were used to adsorb methyl red at a various pH value at room temperature. Similar experiment were conducted using commercially used powder activated carbon (GAC), in order to evaluate the performance of PCSB and PCSBC. It was found that, GAC is very effective in the dye removal at any given pH. While, for both PCSB and PCSBC the initial pH value range from 6 to 10 was favorable. This study had shown that the PCSB and PCSBC could be employed and have a potential for low cost alternative in the wastewater treatment for dyes removal.